Kebudayaan Jawa dan Urgensi Pembangunan Berjati Diri - Slamet Sutrisno (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
The role of Javanese culture for the need of nationaldevelopment is urgent to study seriously. Indonesia structured by,and has a lot of groups, religion and ethnicity which Java formsthe largest one having its long and enchants history. As a nationstate,this country wants to improve existence by means ofdevelopment; by transferred immediately the concepts ofmodernization. In additions to its success Indonesia got greatenough disaster due to the western concepts. Java is very potentialowing to its contents of how to perform development. With thecertainty of national identity we have to explore continuously therich of Javanese culture indicating the ontological,epistemological and ethical values and also concepts of social andpolitical events. Javanese local genius is really very promising.